PENGARUH PROSES BELAJAR DAN KETERSEDIAAN SARANA PENDUKUNG TERHADAP HASIL BELAJAR MAHASISWA SELAMA PANDEMI - Dalimunthe, Muhammad Bukhori; Siti Chairani Lubis, Siti Chairani Lubis (FKIP Unswagati, 2023)
This study aims to analyze the impact of the Covid-19 pandemic on education by focusing on the problem of lack of readiness (students-lecturers) and preparation in the learning process and supporting facilities which will have an impact on the quality of learning outcomes. The method used in this study is a quantitative method with multiple regression analysis techniques to determine the connectedness of the learning process and supporting facilities to learning outcomes. The subjects of this study were students of the 2019 and 2020 economics education study programs, State University of Medan. The data in this study were 60 respondents. The findings of this research state that the Covid 19 pandemic has had an impact on education at State University of Medan, especially for Economics Education study program stamp of 2019 and 2020, where simultaneously the learning process and supporting facilities during the Covid 19 pandemic can affect the quality of learning outcomes for Economics Education study programs at State University of Medan. Partially the learning process during the Covid-19 pandemic had a significant effect on the learning outcomes of students of the Economics Education Study Program stamp of 2019 and 2020 at State University of Medan. And partially the supporting facilities during the Covid-19 pandemic have an effect but are not significant on the learning outcomes of students stamp of 2019 and 2020 Economic Education study program at the State University of Medan